Brønsted Acid Promoted N‐Dealkylation of N‐Alkyl(sulfon)amides. Issue 33 (6th September 2021) - Gu, Linghui; Wang, Yang; Cheng, Zemin; Sun, Yanan; Gong, Xin; Li, Zheyu; Ma, Wenbo
Abstract: A simple and efficient Brønsted‐acid‐promoted N ‐dealkylation of N ‐alkylamides and N ‐alkylsulfonamides has been developed. This strategy features an ample substrate scope with excellent chemical selectivity, affording primary (sulfon)amide derivatives in moderate to good yields without the need for transition‐metal catalysts. Abstract : A simple and efficient Brønsted‐acid‐promoted N ‐dealkylation of N ‐alkylamides and N ‐alkylsulfonamides has been developed. This strategy features an ample substrate scope with excellent chemical selectivity, affording primary (sulfon)amide derivatives in moderate to good yields without the need of transition‐metal catalysts